The Influence of Predisposing, Enabling and Reinforcing on the Participation of the Partners of the Subur (PUS) Become a Iud Kb Acceptor in the Region Tanah Luas Puskesmas Work Kabupaten Aceh Utara - Khalidah, Khalidah; Ginting, Daniel Ginting; Brahmana, Netti Etalia (Sari Mutiara Indonesia University Press, 2018)
The low support of fertile age couples in the IUD KB program has resulted in low interest in IUD acceptors. The preliminary survey of Family Planning Field Officer (PLKB) data in the Extensive Public Health Center in 2017 was 3956 PUS, with active participants of 2053 couples of childbearing age. The achievement is only 57.21% and 42.79% is Unmeet Need. This is a descriptive analytic with a cross sectional design approach. The results showed that there was a relationship between knowledge, attitudes, socio-culture, quality of family planning services, husband's support, and information sources with PUS participation as IUD KB acceptors. In addition, these six variables predominantly influence the participation of fertile age couples (PUS) to IUD family planning acceptors because they have the same high EXP (B) value as other variables. The results of multiple logistic regression tests obtained multivariate analysis of pus women had the opportunity of 4,514 times to participate as IUD KB acceptors. Suggestions The respondents are expected to be able to increase knowledge about IUD family planning so that they are aware of the use of IUD contraceptives and understand the functions, benefits and effectiveness of IUD contraception so that community participants get to know and use IUD contraceptives.